PEMBERDAYAAN PEDAGANG DALAM PENINGKATAN PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT UNTUK PENCEGAHAN PENYEBARAN COVID-19 DI PASAR PAYANGAN - Luh Gede Pradnyawati; Dewa Ayu Putu Ratna Juwita; Ni Made Hegard Sukmawati; Putu Krisna Adwitya Sanjaya (JURNAL SEWAKA BHAKTI, 2021)
Payangan Public Market is one of the largest traditional markets in Gianyar Regency, Bali Province with a total number of 450 traders. The minimum information obtained by traders about the spread of COVID-19 causes their lack of implementation in the implementation of PHBS. According to research results, PHBS is a strategy that can prevent the spread of COVID-19 in the community. Traders must continue to be encouraged to improve PHBS in an effort to prevent the spread of COVID-19. However, in reality, the implementation of PHBS is very minimal in the Payangan Public Market. In addition, the lack of ability of traders to purchase personal protective equipment or PPE such as masks, Face Shields and Hand Sanitizers. This is due to the scarcity of PPE and also their lack of finances, where currently the price of PPE has soared. From the problems faced, the solution that can be offered is the need for a knowledge transfer program about the spread of COVID-19 to find out its prevention with the target of adding knowledge to traders about COVID-19 prevention and increasing the implementation of PHBS. In addition, programs to support the implementation of PHBS include technology transfer and training on how to make PPE, namely Hand Sanitizer, Face Shield and masks. The result of this activity is that partner groups play an active role in every PKM activity with a 100% attendance percentage and 100% active participation. With this activity, there was an increase in the field of understanding about COVID-19 and an increase in the implementation of PHBS through bringing in experts and tutors (coaches) who have assisted traders in the introduction of the COVID-19 virus and the application of clean and healthy living behavior to prevent the spread of the COVID-19 virus. The partner group is also skilled in making PPE in preventing the spread of the COVID-19 virus, namely the manufacture of masks, Hand Sanitizer and Face Shield